Similarity and Difference Between Landscape Character and Townscape: Based on the Hungarian Legal Definitions and Practice - Teremy, Viktória Nóra (4D Tájépítészeti és Kertművészeti Folyóirat, 2022)
The phrases 'townscape' and 'landscape character' are not used very often in common language, although we meet the meaning of these notions day after day. In scientific language, the definitions of settlement and landscape sometimes merge into each other, while at other times are totally different. What do we mean by townscape and what by landscape character? Is it possible to separate the two? The answer is constantly changing during history, according to the spirit of the age and the field of science. Despite the differences and formation, the various approaches converge in many aspects: we always mean a continuously changing, dynamic, spatial, physically distinct visual, and also a geographical spatial unit, which surrounds us. The definition of this, and a deliberate and controlled development are becoming more and more important in landscape and urban planning. At the end of 2016, a new genre, the so called Townscape Design Guide was introduced by law on local planning. In 2016, the national landscape character project had also begun. The phrases in the title refer to these new, national professional ’genres’. The aim of the study is to get to know these two, parallel processes, to reveal their connections by interpreting the Hungarian legal system, and the international background that influences it.